Software Usability Measurement Inventory for Student Information Academic System at Politeknik Negeri Media Kreatif - Yuyun Khairunisa; Sari Setyaning Tyas; Adnan Purwanto; Siti Aisyah (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2020)
Academic information system is a system that is urgently needed by universities to manage academic business processes. State Polytechnic of Creative Media implements SIAM as Student Information Academic System. SIAM being developed has the advantage of being able to convey more detailed information. In addition, SIAM has implemented the SSO (Single Sign On) system where this technology is in great demand, especially in very large and heterogeneous networks. In this research Software Usability Measurement Inventory (SUMI) methods used to conduct usability test. SUMI is a rigorously tested and proven method of measuring software quality from the end user's point of view. The analysis results from SUMI will be used to improve the development of the academic system life cycle.